2012
DOI: 10.2196/jmir.1964
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Combining Web-Based eHealth With Telephone Nurse Case Management for Pediatric Asthma Control: A Randomized Controlled Trial

Abstract: BackgroundAsthma is the most common pediatric illness in the United States, burdening low-income and minority families disproportionately and contributing to high health care costs. Clinic-based asthma education and telephone case management have had mixed results on asthma control, as have eHealth programs and online games.ObjectivesTo test the effects of (1) CHESS+CM, a system for parents and children ages 4–12 years with poorly controlled asthma, on asthma control and medication adherence, and (2) competenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
130
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(131 citation statements)
references
References 61 publications
1
130
0
Order By: Relevance
“…286 The intervention that is most relevant to our study and well described in terms of its underlying theoretical basis is the Comprehensive Health Enhancement Support System (CHESS), an umbrella term for several e-health programmes combining information, adherence strategies, decision-making tools and support services. 287 Pingree et al 284 used the example of CHESS to demonstrate how telehealth interventions are likely to be multifaceted and to depend on a complex interplay between patients, clinicians and the health-care system. Like the Healthlines intervention described here, CHESS was developed by combining several intervention features, each of which had some theoretical justification.…”
Section: Relationship To Previous Studiesmentioning
confidence: 99%
“…286 The intervention that is most relevant to our study and well described in terms of its underlying theoretical basis is the Comprehensive Health Enhancement Support System (CHESS), an umbrella term for several e-health programmes combining information, adherence strategies, decision-making tools and support services. 287 Pingree et al 284 used the example of CHESS to demonstrate how telehealth interventions are likely to be multifaceted and to depend on a complex interplay between patients, clinicians and the health-care system. Like the Healthlines intervention described here, CHESS was developed by combining several intervention features, each of which had some theoretical justification.…”
Section: Relationship To Previous Studiesmentioning
confidence: 99%
“…In this study, trained nurses had the main role in patient education, but were supported by a consultation system that had been previously established by them to form a therapeutic alliance with nephrologists, endocrinologists, and registered dietitians [22]. In order to ensure the quality of patient education, the intervention protocol was designed so that five disease management nurses who possessed knowledge and skills with regard to patient education could carry out the intervention.…”
Section: Quality Assurancementioning
confidence: 99%
“…21 Several tools for assessing asthma control have been developed, but few have been validated for ongoing monitoring, and studies have reported significant limitations in children. [22][23][24][25][26][27] We have developed a new tool, the Asthma Symptom Tracker (AST) or Asthma…”
Section: Discussionmentioning
confidence: 99%
“…17 Several symptom-based short questionnaires have been validated for assessing and monitoring asthma control, but studies have reportedsignificant limitations in children. [22][23][24][25][26][27] For instance, the ACQ has been validated with and without the inclusion of peak flow and has been used for weekly assessment of asthma control. 25,26 The ACT is also a short, easy-to-complete questionnaire and is the most commonly used symptombased tool to assess asthma control.…”
Section: Discussionmentioning
confidence: 99%